Performance Review of Final Waste Processing at Banjarsari Landfill, Bojonegoro Regency in 2024 - Asvinatin Choiriyah; Imam Thohari; Khambali; Sri Anggraeni; Fitri Rokhmalia; Jessika Juan Pramudita (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2024)
The increasing volume of waste entering the Banjarsari Landfill in Bojonegoro Regency has caused serious issues in land management. Evaluating the effectiveness of the sanitary landfill system is crucial to ensuring the sustainability of waste management at the landfill. This research aimed to assess the final waste processing at the Banjarsari Landfill in Bojonegoro Regency in 2024. This descriptive evaluative study used observation, interviews, and measurement methods. Respondents included the head of the waste management division of the Bojonegoro Environmental Office and the manager of the Banjarsari Landfill. The variables examined were waste generation, facilities and infrastructure, waste recording, compaction, soil covering, leachate treatment, and gas handling. The data analysis technique was descriptive, and presented as graphs, diagrams, or tables. The research findings showed that daily waste generation was 55.7 tons, categorized as moderate. The human resources consisted of 18 qualified personnel. The waste recording was done manually, compaction had a ratio of 2:3, waste was covered once a week, leachate was treated with a processing facility, and methane gas was used as a fuel substitute. Implementing a control schedule, improving facilities, and providing outreach and technical training for final waste processing operations were recommended.